2019
DOI: 10.3389/fmicb.2019.02255
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses Provide Insights Into the Evolutionary History and Genetic Diversity of Auricularia Species

Abstract: Species in the genus Auricularia play important roles for people’s food and nutrition especially Auricularia cornea and A. heimuer. To understand their evolutionary history, genome structure, and population-level genetic variation, we performed a high-quality genome sequencing of Auricularia cornea and the corresponding comparative genomic analysis. The genome size of A. cornea was similar to Auricularia subglabra, but 1.5 times larger than that of A. heimuer. Several factors were responsible for genome size v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
(94 reference statements)
0
13
0
Order By: Relevance
“… 9–11 Scarce studies at the intra-genus level have shown that functional diversity between species may arise from diversity in gene content. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“… 9–11 Scarce studies at the intra-genus level have shown that functional diversity between species may arise from diversity in gene content. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…To date, several pathogenic genomes have been sequenced using Pacific Biosciences (PacBio) Sequel or the RSII platform [17,18,20]. With these available genomic sequences, it is possible to determine the evolutionary relationships among fungi [21][22][23][24], as well as to explore the evolution of nutritional mode. In addition, numerous gene clusters associated with pathogenicity have been identified, including secretory proteins, membrane transport proteins, pathogen-host interaction (PHI) genes, fungal virulence factors, and fungal G proteins [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous gene clusters associated with pathogenicity have been identified, including secretory proteins, membrane transport proteins, pathogen-host interaction (PHI) genes, fungal virulence factors, and fungal G proteins [17,18]. In addition, some expanded or contracted orthologous, species-specific genes and positive selective genes, including protein kinases, serine peptidases, cell-wall proteins, carbohydrate-active enzymes (CAZymes), secondary metabolites (SMs), and P450, were shown to be involved in biological control activity, pathogenesis, and mycoparasitism [21,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudeurotium have been reported to have an impact on crop growth promotion and pathogen inhibition ( Zhou et al, 2018 ), and members of Archaeorhizomyces are considered to have the potential to promote the growth of grasslands ( Zhang et al, 2018 ). The genus Auricularia (10 positive and 2 negative links) usually grows on wood and plays an important role in human food supply and nutrition ( Dai et al, 2019 ), which was also significantly promoted by BS75. BS75 demonstrated prominent positive influences of crop growth and pathogen inhibition in the network association analysis.…”
Section: Discussionmentioning
confidence: 99%